Integration of PjBL Models with Inclusive Teaching Styles To Improve Underhand Service Volleyball Skills - Yudhi Ardinnata, Muhammad; Mashud; Warni, Herita (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. This study aims to prove that the integration of the PjBL models with the inclusive teaching style can improve the underhand service volleyball skills. Materials and methods. The research used classroom action research methods. The research design uses the model from Kemmis and Mc. Taggart which consists of 4 stages, namely 1.) Planning, 2.) Implementation of action, 3.) Observation and 4.) Reflection. The research subjects were students of class X A SMA Negeri 1 Salam Babaris with a total of 27 people consisting of 13 boys and 14 girls. Results. Collecting data using quantitative and qualitative techniques. The results of the observation data stated that there was an increase through two cycles. Preliminary observation data shows that 37.04% complete and 68.96% incomplete, then cycle I observation data shows that 59.26% complete and 40.74% incomplete, followed by cycle II observation data shows that 85.18% complete and 14.82% incomplete and has achieved the minimum completeness criterion , namely 80% with KKM 75. Conclusions. It can be proven that the integration of the PjBL models with the inclusive teaching style can improve the underhand service volleyball skills.